School Absenteeism is an Early Indicator of Suicidality in Young People: A Retrospective Longitudinal Matched Case-Control Study Using New Zealand Integrated Data Infrastructure - Zeng, Irene Suilan; Foster, Mandie; Garrett, Nick; Jones, Kelly; Cosmos, Dorothy; Ka'ai, Tania; Ng, Lillian (Elsevier BV, 2026)
Objective School absenteeism, associated with social isolation and loneliness, may signal hidden risks that increase the likelihood of suicidal ideation and behaviors. Few studies have explored longitudinal associations between school absenteeism and suicidality. This study sought to examine longitudinal associations between school absenteeism (a potential early marker) and suicidality to identify other risk and protective factors of students and schools for suicide prevention. Study design Retrospective longitudinal matched case-control study. Methods We used the New Zealand Integrated Data Infrastructure (IDI) database to integrate mental health outcomes with educational data. Based on clinical International Classification of Diseases (ICD) codes and descriptions, we identified 3042 cases from 562,455 students (school year 6–13) enrolled in the education system in 2018, who had a subsequent hospital admission due to suicidality (2019–2021). Cases were matched using a 1:4 ratio with 12,168 control students by sex, school year-level, and ethnicity. Results School absenteeism was significantly associated with subsequent suicidality (adjusted odds ratio (aOR: 2.21, 95% CI 2.02–2.41). Other significant factors included students' post-school activities and previous suicidality; the school's region (secondary/minor urban schools vs. main urban), decile (a socio-economic index), and availability of Māori language learning (level C/D & above vs. not available). Conclusions School absenteeism is an early indicator of suicidality. Combined with other identified student and school factors, a risk stratification strategy for suicide prevention may be established to provide timely early prevention strategies for schools and students at high risk.
Keywords: 1110 Nursing; 1114 Paediatrics and Reproductive Medicine; Nursing; 3213 Paediatrics; 4205 Nursing; School age children; School nursing; Suicide risk; Ethnic groups; Case study